Young Men and Technology: Government Attempts to Create a "Modern" Fisheries Workforce in Newfoundland, 1949-1970 - Wright, Miriam (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1998)
In the years following World War II, the Newfoundland fishing economy was transformed from a predominantly inshore, household-based, saltfish-producing enterprise into an industrialized economy dominated by vertically-integrated frozen fish companies. The state played a critical role in fostering this transformation, and one aspect of its involvement was the creation of a "modern" fisheries workforce. Although women's labour had historically been an integral part of the inshore fishery, state planners assumed that women would withdraw from direct involvement in economic activities. Indeed, the male bread-winner model, the dominant gender ideology of western culture (but not of Newfoundland outport culture at the time), was embedded in state economic policies for the Newfoundland fishery in the post-World War II period. Training men to become more efficient, technologically-trained harvesters and offshore trawler workers became central concerns. Although the attempts to recruit young men as trawler crews were not entirely successful, this and the other examples of the government's mediating role helps illustrate the complexity of economy, state and gender ideology, all involved in the construction of a new fisheries workforce.